“Begotten” and “Created”. The Synod of Ancyra (358 C.E.) on the Perfect Birth of the Son of God (2021)
The present article seeks to reconstruct the Christological meaning of the verbs “creating” and “begetting” in the Synodical letter of Ancyra (358). In order to assess the teaching of this document, the first part of the article provides an overview of th